Current Status of Breast Organoid Models - Mohan, Srivarshini Cherukupalli; Lee, Tian-Yu; Giuliano, Armando E.; Cui, Xiaojiang (Frontiers in Bioengineering and Biotechnology, 2021)
Breast cancer (BC) is the most frequently diagnosed malignancy among women globally. Although mouse models have been critical in advancing the knowledge of BC tumorigenesis and progression, human breast models comprising the breast tissue microenvironment are needed to help elucidate the underlying mechanisms of BC risk factors. As such, it is essential to identify an ex vivo human breast tissue mimetic model that can accurately pinpoint the effects of these factors in BC development. While two-dimensional models have been invaluable, they are not suitable for studying patient-specific tumor biology and drug response. Recent developments in three-dimensional (3D) models have led to the prominence of organized structures grown in a 3D environment called “organoids.” Breast organoids can accurately recapitulate the in vivo breast microenvironment and have been used to examine factors that affect signaling transduction, gene expression, and tissue remodeling. In this review, the applications, components, and protocols for development of breast organoids are discussed. We summarize studies that describe the utility of breast organoids, including in the study of normal mammary gland development and tumorigenesis. Finally, we provide an overview of protocols for development of breast organoids, and the advantages and disadvantages of different techniques in studies are described. The included studies have shown that breast organoids will continue to serve as a crucial platform for understanding of progression of BC tumors and the testing of novel therapeutics.